Crescimento, morfologia, partição de assimilados e produção de matéria seca do feijão (Phaseolus vulgaris L) submetido a três níveis de densidade do fluxo radiante - Fernandes Lopes , Nei; Oliva , Marco Antonio; Melges , Elena; Furtado , Marcio Henrique; de Freitas , José Guilherme (Revista Ceres, 2025)
Growth, morphology and dry matter partition were studied in Phaseolus vulgaris L., cv. Negrito 897, under three light levels (30, 62 and 100% of sunlight) in the greenhouse. The plants were harvested at 10 — day intervals.